The influence of special interests and party activists on electoral competition - Nicolas-Guillaume Martineau (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the effects on electoral competition of political parties relying on monetary donations and volunteer labour for their electioneering activities. It also examines whether a recorded decline in party activism increases special-interest influence on party policy platforms. Parties are shown to choose differentiated platforms in equilibrium when activists are present, despite factors drawing them together. Special-interest influence on platforms increases when a decline in activism stems from a fall in their motivation, following parties relying less upon them. This reduces procedural welfare, and potentially reduces voter welfare on policy outcomes, thus calling for more strict electoral laws.
Keywords: D71; D72; 330; activism; special-interest politics; political participation; collective action; electoral competition; electoral financing laws; welfare